NEYMAR - Caioli, L. (Luca), 1958- (London : Icon Books Ltd., 2020)
This is Wayne Rooney's first hand account of his 10 years playing at the highest level in English football - and for the biggest club in the world. This is his inside story of life on the pitch for Manchester Utd.; the League titles, FA Cups, League Cups and Champions League adventures. Originally published: 2012.
Keywords: Neymar, -- 1992-; Soccer players -- Brazil -- Biography; Soccer players -- Spain -- Biography; Sport; Biographies; Biography